The Role and Mechanism of Erythrocyte Invasion by Francisella tularensis - Schmitt, Deanna M.; Barnes, Rebecca; Rogerson, Taylor; Haught, Ashley; Mazzella, Leanne K.; Ford, Matthew; Gilson, Tricia; Birch, James W.-M.; Sjöstedt, Anders; Reed, Douglas S.; Franks, Jonathan M.; Stolz, Donna B.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis is an extremely virulent bacterium that can be transmitted naturally by blood sucking arthropods. During mammalian infection, F. tularensis infects numerous types of host cells, including erythrocytes. As erythrocytes do not undergo phagocytosis or endocytosis, it remains unknown how F. tularensis invades these cells. Furthermore, the consequence of inhabiting the intracellular space of red blood cells (RBCs) has not been determined. Here, we provide evidence indicating that residing within an erythrocyte enhances the ability of F. tularensis to colonize ticks following a blood meal. Erythrocyte residence protected F. tularensis from a low pH environment similar to that of gut cells of a feeding tick. Mechanistic studies revealed that the F. tularensis type VI secretion system (T6SS) was required for erythrocyte invasion as mutation of mglA (a transcriptional regulator of T6SS genes), dotU, or iglC (two genes encoding T6SS machinery) severely diminished bacterial entry into RBCs. Invasion was also inhibited upon treatment of erythrocytes with venom from the Blue-bellied black snake (Pseudechis guttatus), which aggregates spectrin in the cytoskeleton, but not inhibitors of actin polymerization and depolymerization. These data suggest that erythrocyte invasion by F. tularensis is dependent on spectrin utilization which is likely mediated by effectors delivered through the T6SS. Our results begin to elucidate the mechanism of a unique biological process facilitated by F. tularensis to invade erythrocytes, allowing for enhanced colonization of ticks.